Summary of Peanut Insecticide Options for Florida - Henry E. Jowers; Richard K. Sprenkel (EDIS)
Management of insect pests of peanut in Florida occasionally requires the use of insecticides. This publication was prepared to provide the user with a summary of available insecticide options for the major insects pests which may be encountered. This document is ENY-708, one of a series of the Entomology and Nematology Department, Florida Cooperative Extension Services, Institute of Food and Agricultural Sciences, University of Florida. Publication date: May 2004.